The effectiveness of using the teachy digital application on elementary school students’ science achievement - Muhammad Noryanto; Oktaviani Adhi Suciptaningsih; Riska Pristiani (Journal of Research in Instructional, 2026)
Low engagement and conventional instruction remain obstacles in Indonesian elementary science. This study examined the effectiveness of Teachy, a technology-enhanced learning application, in Grade-5 science. A quasi-experimental nonequivalent control group design was implemented at SDN V 013 Tana Tidung (N=33). The experimental class (n=17) learned with Teachy (interactive quizzes, animations, automated feedback); the control class (n=16) received conventional teaching. Outcomes were measured with a validated 25-item multiple-choice post-test; student engagement was observed during lessons. Assumptions of normality (Kolmogorov–Smirnov/Shapiro–Wilk) and homogeneity (Levene) were met; analyses used independent samples t-tests (α=.05). Results showed higher performance for Teachy (M=83.6, SD=6.8) than control (M=74.2, SD=7.5), t(31)=3.776, p<.001, mean difference=9.40, 95% CI [4.32, 14.48], Hedges’ g=1.28 (large). Findings indicate that Teachy substantially improves science achievement and supports constructivist learning aligned with the Merdeka Curriculum. Implications include integrating Teachy as core media with formative monitoring; future studies should extend to multi-site, pretest–posttest designs and retention tests.